2007
DOI: 10.1093/gerona/62.9.1002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Community Occupational Therapy on Quality of Life, Mood, and Health Status in Dementia Patients and Their Caregivers: A Randomized Controlled Trial

Abstract: Community occupational therapy should be advocated both for dementia patients and their caregivers, because it improves their mood, quality of life, and health status and caregivers' sense of control over life. Effects were still present at follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
228
1
16

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(250 citation statements)
references
References 21 publications
5
228
1
16
Order By: Relevance
“…For both caregivers and recipients mood, quality of life, and health status improved. In carerecipients daily functioning improved [51,89].…”
Section: Individual Based Occupational Therapy Interventionsmentioning
confidence: 98%
“…For both caregivers and recipients mood, quality of life, and health status improved. In carerecipients daily functioning improved [51,89].…”
Section: Individual Based Occupational Therapy Interventionsmentioning
confidence: 98%
“…5 After the recommendations from the consensus conference were finalized, the results of a single-blind randomized controlled trial of community-based occupational therapy for older patients with mild to moderate dementia and their primary caregiver were published. [6][7][8] The therapy comprised environmental modifications, compensatory strategies for the patient, and training of the caregiver to use effective supervision, problemsolving and coping strategies to sustain the autonomy and social participation of the patient and the caregiver. After 10 one-hour sessions over 5 weeks, statistically significant improvements were seen in the short term (3 months) in the daily functioning of patients in the intervention group.…”
Section: Nonpharmacologic Therapymentioning
confidence: 99%
“…Graff et al [8] reported that the COPE was effective for improving BPSD, especially depressive mood, among clients with dementia as well as the depressive mood among caregivers. Similarly, Gitlin et al [12] reported that the TAP was effective in improving the BPSD of clients with dementia, especially agitation and argumentation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Graff and colleagues [7,8] went on to examine the program's effectiveness via a randomized controlled trial (Dutch study). The program comprised 10 one-hour occupational therapy sessions over five weeks, and included the use of devices to compensate for clients' cognitive decline as well as cognitive behavioral interventions for caregivers that aimed at improving coping behavior and supervision of clients.…”
Section: Literature Reviewmentioning
confidence: 99%